Apropriações nos territórios curriculares: cartografando de-formações na história da arte - Dahmer, Carin Cristina (2017)
This master’s thesis aims at approaching possible curricula through a school curriculum experienced by articulating the theme of art history in elementary school. Appropriation processes of school planning are considered along with relations among the concepts of rhizome, lines, and body without organs by Deleuze and Guattari (2011, 2012). The way the research was developed was through the displacement between experiences as teacher-student, the school and graduate spaces. We aimed to promote a rhizomatic curriculum (GALLO, 2007), and problematize it through de-formation (SILVA, 2004), in relation to its possible deviations. Thus, processes of appropriation, according to Archer (2012), Argan (2006) and Chiarelli (2002), present possibilities for inventing a curriculum in the educational field, with the philosophy of difference by Deleuze and Guattari’s writings. This research problematization is related to the question: What can the curriculum do between appropriation and art history, and what can appropriation do to de-form the curriculum and art history? The methodology used was cartography as a way to produce paths of a teaching process about to happen. The lines that articulate the curriculum in visual arts are inscribed as an experience, a possibility, facing the different paths that each teaching experience designs to itself.